Linear viscoelastic creep compliance and retardation spectra of bitumen impregnated fiberglass mat and polymer modified bitumen. (30th November 2017) - Rajan, Sreehari; Sutton, Michael A.; Oseli, Alen; Emri, Igor; Matta, Fabio
Highlights: Creep compliance of bitumen impregnated fiberglass mat (BIFM) is investigated. Creep response of BIFM is compared with polymer modified bitumen (PMB) sample. Results show significant improvement in the performance of BIFM at higher temperatures. Retardation spectra obtained are capable of accurately reconstructing creep response. Abstract: Temperature-controlled experiments are performed to characterize the viscoelastic response of materials commonly used in asphalt roofing shingles, including both creep compliance master curves and shear retardation spectra. Material systems characterized in this study include polymer modified bitumen (PMB) and bitumen impregnated fiberglass mat (BIFM). BIFM experiments are conducted using 3-point bend specimens in a TA instruments RSA III DMA, whereas PMB results are obtained from torsional loading of two cylindrical specimens in a MARS II controlled stress rheometer. Short term (duration of 1000 s) isothermal creep experiments are conducted at temperatures above the bitumen glass transition (Tg = −42 °C) (a) on BIFM specimens in the range −30 °C ≤ T ≤ 30 °C and (b) on PMB specimens in the temperature range −30 °C ≤ T ≤ 20 °C. Using the time-temperature superposition principle (TTSP), creep compliance master curves for both materials are obtained at a reference temperature of 0 °C. The results are then used to obtain the shift factors and develop both Williams-Landel-Ferry (WLF) and Arrhenius models. Results show that BIFM has ≈ 2.2X lower creep compliance than PMB at T = 0 °C, with the difference increasing at higher temperatures. Furthermore, beyond the early, short-term creep times, significant deviations between the retardation spectra of BIFM and PMB are observed.